2022
DOI: 10.7150/thno.73746
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine-mediated LDHA induction potentiates chemoresistance of colorectal cancer cells through metabolic reprogramming

Abstract: Background: Chemoresistance to 5-fluorouracil (5-FU) is a major barrier to influence the treatment efficiency of colorectal cancer (CRC) patients, while the precise molecular mechanisms underlying 5-FU resistance remain to be fully elucidated. Methods: The metabolic profiles including ATP generation, glucose consumption, lactate generation, and oxygen consumption rate (OCR) in 5-FU resistant CRC cells were compared with those in their parental cells. Subsequently, a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…As the most widely recognized methylase reader, YTHDF1 has been investigated in many scientific research fields. Recent studies have shown a strong correlation between hypoxia and YTHDF1, and clinical evidence proves that YTHDF1 is associated with cancer progression and can maintain hypoxia tolerance by promoting the translation of certain proteins [ 31 , 32 , 33 ]. It has been shown that YTHDF1 expression upregulated in a HIF-1α-dependent manner by promoting transcription in human hepatocellular carcinoma [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the most widely recognized methylase reader, YTHDF1 has been investigated in many scientific research fields. Recent studies have shown a strong correlation between hypoxia and YTHDF1, and clinical evidence proves that YTHDF1 is associated with cancer progression and can maintain hypoxia tolerance by promoting the translation of certain proteins [ 31 , 32 , 33 ]. It has been shown that YTHDF1 expression upregulated in a HIF-1α-dependent manner by promoting transcription in human hepatocellular carcinoma [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MLH1 expression could be down-regulated by the GPR81-cAMP-PKA-CREB axis to promote chemotherapy tolerance ( Figure 2 ), and targeted inhibition of lactate production in C. tropicalis may improve the therapeutic effect ( 111 ). Increased levels of m 6 A and METTL3 were found in 5-FU resistant CRC cells, and targeted inhibition or knockdown of METTL3 could inhibit glycolysis in cancer cells and restore chemo-sensitivity to 5-FU in resistant CRC cells ( 112 ). The evidence highlighted that METTL3 enhanced LDHA expression, catalyzing the conversion of pyruvate to lactate, thereby promoting glycolysis and enhancing chemotherapy tolerance to 5-FU in tumor cells.…”
Section: Effect Of Lactic Acid On Chemoresistance Of Crcmentioning
confidence: 99%
“…The evidence highlighted that METTL3 enhanced LDHA expression, catalyzing the conversion of pyruvate to lactate, thereby promoting glycolysis and enhancing chemotherapy tolerance to 5-FU in tumor cells. METTL3/LDHA axis-induced glucose metabolism may be a potential therapeutic target for CRC cells to overcome 5-FU resistance ( 112 ), which was demonstrated to be associated with overexpression of GLUT1 in colon cancer cells. Inhibition of GLUT1 by the specific inhibitor WZB117 significantly increases the sensitivity of 5-FU-resistant cells to chemotherapeutic agents ( Figure 2 ), providing an additional therapeutic option for patients with 5-FU-resistant colon cancer ( 113 ).…”
Section: Effect Of Lactic Acid On Chemoresistance Of Crcmentioning
confidence: 99%
“…The m 6 A modification involves three kinds of crucial protein factors, including methyltransferases (writers), demethylases (erasers), and methylation-binding proteins (readers) (48). To date, only one study revealed that the writer METTL3 enhanced the expression of LDHA (49). Mechanistically, the coding sequence (CDS) of LDHA mRNA is the methylation region for m 6 A, rather than 5′untranslated region (5′-UTR) or 3′-UTR.…”
Section: N6-methyladenosine Rna Methylationmentioning
confidence: 99%
“…Mechanistically, the coding sequence (CDS) of LDHA mRNA is the methylation region for m 6 A, rather than 5′untranslated region (5′-UTR) or 3′-UTR. Then, METTL3 induced the LDHA transcription via the stabilization of the mRNA of hypoxia-inducible factor (HIF)-1a, further enhancing the YTH domain-containing family protein 1 (YTHDF1)-mediated translation of LDHA (49). However, more efforts are needed to elucidate the regulatory effect of the m 6 A modification of LDHA.…”
Section: N6-methyladenosine Rna Methylationmentioning
confidence: 99%